Evaluating EMI of Unshielded Cables in High Frequency GaN Inverter Application - Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas; Diepold, Fabian (2021 Joint IEEE International Symposium on Electromagnetic Compatibility Signal and Power Integrity, and EMC Europe, EMC/SI/PI/EMC Europe 2021, 2021)
Inverters in VSDs represent a common source of EMI. The steep voltage slopes of modern power electronics with their high frequency share can cause radiated emissions. Therefore, shielded motor cables are used to minimize these emissions. However, in order to reduce costs, unshielded cables are an attractive option. This paper analyses an inverter setup with different motor cables. A measurement setup is presented in order to investigate the proper PE connection for complying with the standards.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Cable shielding; Electromagnetic Compatibility; Inverters; Radiated emissions